Untangling the role of social relationships in the association between caregiver burden and caregiver health: an observational study exploring three coping models of the stress process paradigm - Hannah Tough; Martin W. G. Brinkhof; Christine Fekete (BMC, 2022)
Abstract Background Caregivers health is often at risk due to the detrimental effects of caregiver burden. It is therefore vital to identify strategies and resources, which ensure the safeguarding of caregivers' health, whilst also enabling caregivers to continue providing high quality long-term care to care-receivers. The objective of this study is therefore to examine the moderating and mediating role of different social relationship constructs (social networks, social support, relationship quality, and loneliness) in the relationship between subjective caregiver burden and health, by exploring different coping models of the stress process paradigm, namely the stress buffering, social deterioration and counteractive models. Methods Longitudinal survey data from 133 couples of caregiving romantic partners and persons with spinal cord injury, living in Switzerland were used. We employed multivariable regression analysis with the inclusion of interaction terms to explore moderation effects of social relationships (i.e. stress buffering model), and path analysis to explore mediation effects (i.e. social deterioration vs. counteractive model) of social relationships on the association between subjective caregiver burden and health. Health was operationalised using the following outcomes: mental health, vitality, bodily pain and general health. Results Social support and relationship quality were found to buffer the negative effects of subjective caregiver burden on mental health. Mediating effects of social relationships were observed for mental health (indirect effect -0.25, -0.42- -0.08) and vitality (indirect effect -0.20, -0.37- -0.03), providing support for the deterioration model. Loneliness was found to be a particularly important construct on the pathway from caregiver burden to health. Conclusion Our study highlights the potential of social support and relationship quality to override the negative consequences of caregiver burden on mental health and vitality. Our evidence thus supports the advance of interventions that seek to improve qualitative aspects of social relationships, especially in caregivers experiencing a high subjective caregiver burden.